(untitled) (Biological Sciences - PJSIR, 2005)
The lipolytic enzymes (lipase and phospholipase) extracted from the defatted seeds of Carica papaya showed optimum activity at 40 °C and pH 7 in aqueous media. n-Heptane was found to be the most satisfactory solvent to maximize activities of lipase and phospholipase. The activity of lipase extracted from germinated seeds increased with the stage of seed development, but the phospholipase activity was noted to decrease.